Parents and children relationships in social networking : an analysis from Islamic perspective. - Khasanah, Ana Uswatun; Paiizi, Madihah; Nasoha, Nurnajihan; Noordin, Noor Salina; Sari, Maya Novia; Muhammad, Muhd. Rosydi (IIUM Press, 2011)
The emergence of new technologies presents huge challenges to the role of parents in gUiding their children. In this paper, we will discuss some issues and problems in social networking sites used by children. We found that parents worry about their children's activity on the internet. On the other hand kids do not want their freedom to be restricted by their parents. The paper also highlights the importance of parents' involvement in their kids' day to day activities as well as monitoring their children activities on the internet. We discussed several suggestions to bridge between both parties to build a healthy parent-child relationship, avoid conflict, and build trust in accordance to Islamic teachings.